Efeito de tratamentos térmicos no comportamento em fadiga de fios de NiTi superelásticos - Jéssica Dornelas Silva (2019)
Near-equiatomic NiTi alloys rich in Ni are functional alloys of great commercial relevance. Within their applications, these alloys are commonly subjected to cyclic efforts and, thus, to failure by fatigue. Este trabalho tem como motivação principal o uso de limas endodônticas, as quais estão sujeitas a condições agressivas de deformação cíclicas. The present work has as motivation the use of NiTi in endodontic files, which undergo aggressive conditions of cyclic deformation. Efforts have currently being made in the files design optimization and heat treatment performance in the wires from which they are manufactured or in the files themselves, producing instruments with an even higher performance than the traditional superelastic instruments. However, a better understating about the performed heat-treatments and the fatigue mechanisms are still scarce. In this context, this work has the aim of contributing to a better metallurgical comprehension of the mechanical effects obtained through heat-treatments of near equiatomic NiTi wires rich in Ni, relating ageing heat-treatments, the microstructure achieved through them and the resultant mechanical properties in an aggressive fatigue condition. For that, annealing heat treatments have been performed in diferent temperatures and the low cycle fatigue life was evaluated. Tension testes and X-ray diffractometry were performed for mechanical and microstructural characterization, respectively, and differential scanning calorimetry was realized to determinate the transformation temperatures. Subsequently, the heat-treatment conditions which provided the higher fatigue lives were repeated and fatigue tests in varying deformation amplitudes and temperatures were performed in order to evaluate the influence of these variables as well as the effect of the present phases for a fixed thermomechanical state. The results obtained showed that aging treatments are effective in increasing the fatigue life of superelastic NiTi wires, especially when the presence of the R-phase is achieved. These improvements were attributed to the behavior of these microstructures during mechanical cycling and to the differences during crack propagation: while austenitic wires undergo a high amount of defect accumulation, wires constituted by the R-phase have cracks ramification through the variants interfaces.